Psychological distress of Filipino deaf: Role of environmental vulnerabilities, self-efficacy, and perceived social support - Sintos, Marcella L. (Animo Repository, 2017)
Researches on deaf mental health exemplify that deaf individuals are two to three times more vulnerable to psychological distress not because of their deafness per se, but because of their interactions in the hearing world. Throughout their lifespan, they have been exposed to several environmental vulnerabilities such as hearing parents, communication barriers, additional disabilities, and lack of mental health services. Using the assumptions of stress-vulnerability-protective factors model of Liberman (2008), moderation analyses were performed to prove the moderating role of general self-efficacy and perceived functional social support on the effect of vulnerabilities in their psychological distress. 120 self-contained Deaf college students aged 18 to 25 (M=21.83; SD=4.11) participated in the study. Using the instruments that were administered in Filipino Sign Language, results show that (1) there is a non-significant relationship between environmental vulnerabilities and psychological distress, and (2) general self-efficacy and perceived functional support do not act as moderators. This entails inapplicability of Libermans (2008) framework, which may be attributed to (1) normalization of environmental vulnerabilities in Deaf culture, (2) occurrence of inconsistent mediation in perceived functional social support, and (3) unique context of Deaf individuals in being in a hearing society. These findings lead to various recommendations in research and practice that aim to support the mandates of UNCRPD and Magna Carta for PWDs. Limitations in this study are also discussed.